The Factors Affecting Development of Marketing Capability of Collegiate Sport - Rasoul Tarighi; Mehrzad Hamidi (The Society of Aging and Physical Activity (SAPA), 2017)
Background. Now one of the necessary capabilities, to succeed in the field of competition is having knowledge and marketing skills in economic institutions. Objectives. The goal of this study was Factors affecting development of marketing capability of collegiate sport. Methods. This study is correlating, and, in view of objective, current research is practical. Populations consist of 5 groups which involve previous and present executive committee, administers of provincial committees, experts and employers of National University Sport Federation, headmen and experts of Sport administration and Sports directors of further education section of universities, contain governmental universities, Azad, Payam Noor, Practical and scientific, Hygiene and Therapy and Medical Science universities, and some members of the faculty of universities. In regard to limitation of populations, sampling method is all-counting. Results. The result showed that the totality of confirmatory factor analysis model have necessary fitting (GFI=0.90, RMSEA=0.045, p<0.001). The Results Showed that factor's include management capability(T=16.06), marketing staff (T=14.81), marketing strategy (T=14.57), marketing information system (T=12.57), marketing organization (T=12.56), and branding capability (T=12.17), with significant Priorities respectively, were effective factor's on marketing capability of National University Sports Federation of Islamic Republic of Iran. Also, marketing capability (T=11.10) has a positive and significant effect on marketing performance of National University Sports Federation. Conclusion. According to obtained results from Opinions of university sport specialists and experts, it seems that managers of university sport should have Pay more attention to identified factors of university sport development that Which ranked respectively had the highest impact factor (Such as management capability, marketing staff and marketing strategy).